Pharmacokinetic Evaluation of Eltrombopag in ITP Pediatric Patients - Marco Dionisi; Sara Cairoli; Raffaele Simeoli; Francesca De Gennaro; Valeria Paganelli; Roberto Carta; Francesca Rossi; Carlo Dionisi-Vici; Giuseppe Palumbo; Giuseppe Palumbo; Bianca Maria Goffredo (Frontiers Media S.A., 2021)
Background: Eltrombopag (EPAG) is an oral thrombopoietin receptor agonist, approved for refractory primary immune thrombocytopenia (ITP) in pediatric patients. In two pediatric RCTs, EPAG led to an improvement of platelet counts and a reduction in bleeding severity. However, a significant number of pediatric patients did not achieve the primary endpoints. We performed a pharmacokinetic evaluation of EPAG in pediatric patients with refractory ITP.Methods: Outpatients aged from 1 to 17 y, affected by refractory ITP to first-line treatment, were enrolled for a pharmacokinetic assessment. The analysis of drug plasma concentration was performed by the LC-MS/MS platform. Non-compartmental and statistical subgroup analyses were carried out using the R package ncappc.Results: Among 36 patients eligible for PK analysis, the median dose of EPAG given once daily was 50 mg. The EPAG peak occurs between 2 and 4 h with a population Cmax and AUC 0-24 geo-mean of 23, 38 μg/ml, and 275, 4 µg*h/mL, respectively. The pharmacokinetic profile of EPAG did not show a dose proportionality. Female patients showed a statistically significant increase of dose-normalized exposure parameters, increasing by 110 and 123% for Cmax and AUC 0-24, respectively, when compared to male patients. Patients aged 1-5 y showed values increased by more than 100% considering both exposure parameters, compared to older children. Furthermore, patients presenting complete response (83%), showed augmented EPAG exposure parameters compared to subjects with partial or no response.Conclusion: These data highlight the need to further explore the variability of EPAG exposure and its pharmacokinetic/pharmacodynamic profile in pediatric patients also in a real-life setting.